2021
DOI: 10.2147/ppa.s330842
|View full text |Cite
|
Sign up to set email alerts
|

Medication Belief is Associated with Improved Adherence to Exclusive Enteral Nutrition in Patients with Crohn’s Disease

Abstract: Background:The prevalence of Crohn's disease (CD) has been increasing rapidly in China, and the role of exclusive enteral nutrition (EEN) in the management of adult patients with active CD is evolving. Adherence is a key factor in the effective treatment of many chronic diseases. Aim: The aim of this study was to assess adherence to EEN of CD patients and to evaluate the relationship between medication belief and EEN adherence. Methods: A cross-sectional study was conducted, and demographic information, adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…A meta-analysis showed that if the patient has a higher belief in the necessity of taking medicine and a lower belief in the concern of harmfulness, the patient will show better adherence ( Adem et al, 2021 ). In recent years, our research teams have focused on the medication adherence in IBD patients, we found medication belief is associated with improved adherence to exclusive enteral nutrition in patients with CD patients ( Li et al, 2021 ). However, adherence to IFX among Chinese CD patients and its association with medication belief remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis showed that if the patient has a higher belief in the necessity of taking medicine and a lower belief in the concern of harmfulness, the patient will show better adherence ( Adem et al, 2021 ). In recent years, our research teams have focused on the medication adherence in IBD patients, we found medication belief is associated with improved adherence to exclusive enteral nutrition in patients with CD patients ( Li et al, 2021 ). However, adherence to IFX among Chinese CD patients and its association with medication belief remain unclear.…”
Section: Introductionmentioning
confidence: 99%